ANALISIS PENGARUH AKTIVITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hendayana, Yayan; Anjarini, Dianita (Mediastima, 2021)
The purpose of this study was to determine and analyze the effect of Activity (Working Capital Turnover / WCT), Liquidity (Current Ratio / CR), and Solvency (Debt to Asset Ratio / DAR) on profitability (Return On Asset / ROA). Determination of the sample using purposive sampling technique based on predetermined criteria obtained as many as 13 companies with a research period of 5 years (2015-2019). The test method uses panel data regression analysis with Eviews version 9. Based on the results it is known that WCT has a positive and insignificant effect on ROA, CR has a significant positive effect on ROA, and DAR has a negative and insignificant effect on ROA of construction and building companies listed on the Indonesia Stock Exchange for 2015-2019 period.